Role of lattice inhomogeneities on the electronic properties of selenium deficient Bi2Se3. (12th October 2017) - Tayal, Akhil; Kumar, Devendra; Lakhani, Archana
Abstract: Inter-layer coupling is widely considered to play a crucial role in tuning electronic properties of 3D topological insulators. The aim of this study is to evaluate the role of crystallographic defects on inter-layer coupling in the Se deficient Bi2 Se3 (0 0 3) crystal using extended x-ray absorption fine structure spectroscopy (EXAFS) technique. EXAFS measurements at Se–K and Bi–L3 edges reveal distinct local geometry around these atomic sites. It has been observed that short inter-layer Bi–Se and Se–Se bonds emerge in the sample. This additional structural motif coexists with the conventional crystallographic arrangement. Within the quintuple layer Bi–Se bonds are preserved with slight compression in intra-planer Bi–Bi and Se–Se distance and overall reduction in c / a ratio. These findings suggest formation of deformed lattice region, localized and dispersed inhomogeneously within the sample. Such inhomogeneities have also resulted in interesting transport properties such as quantum Hall effect (QHE), large linear magnetoresistance and π -Berry phase in Shubnikov-de Haas (SdH) oscillations of bulk crystals. Detailed analyses of magnetotransport measurements suggest that tuning of inter-layer coupling by local lattice deformation is the key factor for unusual transport properties. Role of axial strain, and stacking faults generated due to defects and charged Se vacancies are discussed to understand the observed electronic properties.